Comparative Study of Antioxidant, Antidiabetic, Cytotoxic Potentials, and Phytochemicals of Fenugreek (Trigonella foenum-graecum) and Ginger (Zingiber officinale) - Javaria Hafeez; Muhammad Naeem; Tayyab Ali; Bushra Sultan; Fatma Hussain; Haroon Ur Rashid; Muhammad Nadeem; Ibrahim Shirzad (Journal of Chemistry)
Trigonella foenum-graecum and Zingiber officinale are used as traditional medicinal plants for the treatment of infectious and inflammatory diseases. However, a comparative analysis and bioactivities of T. foenum-graecum and Z. officinale lack some necessary information for therapeutic purposes. This study was designed to evaluate the biochemical characterizations and biological efficacy of T. foenum-graecum and Z. officinale as antioxidant, antidiabetic, antiamnesic, and cytotoxic agents. Antioxidant activity was determined by DPPH free radical scavenging assay. Antidiabetic potentials were evaluated by glycation, alpha-amylase, and acetylcholinesterase inhibition assays. We performed biochemical characterization through analyses of high-performance liquid chromatography (HPLC) and FTIR (Fourier transform infrared spectroscopy). Results revealed that total phenolic contents (TPCs) (g GAE/100 g) of T. foenum-graecum and Z. officinale were 5.74 ± 0.81 g and 6.15 ± 0.06 g, respectively, and total flavonoid contents (TFCs) varied from 1.51 ± 0.58 g CE/100 g to 17.54 ± 0.58. DPPH scavenging potentials of T. foenum-graecum and Z. officinale extract were 50.27% and 88.82%, respectively. Antiglycation potentials of T. foenum-graecum and Z. officinale showed a maximum activity at 16–29% and 96%. Alpha-amylase and alpha-glucosidase inhibition ranged from 9.43–24.95 and 10.52–27.89 and 54.97%, respectively. All the test samples of T. foenum-graecum and Z. officinale showed acetylcholinesterase inhibition potential at 0.37–46.88%. HPLC analysis of T. foenum-graecum revealed the presence of quercetin, gallic acid, caffeic acid, vanillic acid, syringic acid, and cumeric acid, while Z. officinale revealed the quercetin, gallic acid, vanillic acid, benzoic acid, chlorogenic acid, p.Coumaric acid, ferulic acid, and cinnamic acid. FTIR analysis revealed the presence of aldehydes, ketones, aromatic compounds, amines, and carbonyl groups in T. foenum-graecum, while alcohol, alkane, alkene, ketone, amine, and ether are bioactives present in the methanolic extract of Z. officinale. It was concluded that a comparative analysis of T. foenum-graecum and Z. officinale showed that Z. officinale showed higher therapeutic effects.